Controlled synthesis of end-functionalized mannose-6-phosphate glycopolypeptides for lysosome targeting - Das, Soumen; Parekh, Nimisha; Mondal, Basudeb; Sen Gupta, Sayam (ACS Macro Letters, 2016)
The ubiquitous expression of the mannose-6-phosphate receptor on the majority of human cells makes it a valid target in the quest to deliver therapeutics selectively to the lysosome. In this work end-functionalized polyvalent mannose-6-phosphate glycopolypeptides (M6P-GPs) with high molecular weights (up to 22 kDa) have been synthesized via NCA polymerization. These synthetic M6P-GPs were found to display minimal toxicity to cells in vitro and show exceptional selectivity for trafficking into lysosomes in various cell lines. Comparison of the cellular uptake behavior of M6P-GP and the corresponding mannose-GP polymer reveals that incorporation of the phosphate moiety at the 6-position of mannose completely alters its trafficking behavior and becomes exclusively lysosome specific. We also demonstrate that trafficking of M6P-GPs in mammalian cells is likely associated with the CI-MPR receptor pathway.